Parameters of the UNIQUAC model for describing the vapor-liquid phase equilibrium of D2-T2, D2-DT, DT-T2 hydrogen isotope mixtures - T. G. Korotkova (Тонкие химические технологии, 2023)
Objectives. Determination of the parameters of the binary energy interaction of the (UNIversal QUAsiChemical) UNIQUAC model on the basis of mathematical processing of experimental literature data on the phase equilibrium of hydrogen isotopic mixtures D2-T2, D2-DT, DT-T2 to calculate the activity coefficients of the components D2, DT, and T2.Methods. The method of successive approximations was used in junction with the “from stage to stage” method, which consists in calculating a single evaporation process on a theoretical plate.Results. Equations were written for calculating the activity coefficients of hydrogen isotopes on the basis of the Sherwood theory as applied to binary D2-T2, D2-DT, DT-T2 and ternary D2-DT-T2 hydrogen isotope mixtures. The graphical dependences of the activity coefficients and separation coefficients of mixtures D2-T2, D2-DT, and DT-T2 are compared in the range of the concentration of a highly volatile component from 0 to 100 mol % at atmospheric pressure for three options: ideal mixtures; non-ideal mixtures using the Sherwood theory; non-ideal mixtures on the basis of the UNIQUAC model. The dependences of the separation coefficients a were found to be similar for all binary isotopic mixtures. However, when considering mixtures as ideal, a increases.According to Sherwood's theory, a remains a practically constant value, which is independent of the composition of the mixture. The UNIQUAC model predicts a decrease in a with an increase in the concentration of a less volatile component in the mixture. The profile of the distribution of hydrogen isotopes D2, DT, and T2 of a three-component mixture D2-DT-T2, along the height of a distillation column operating in a closed mode was calculated for three variants. It was accepted that: pressure along the height of the column is constant and equal to atmospheric 760 mm Hg. Art.; number of theoretical plates 21; concentration of components in the liquid phase on the first plate (stage), in mol %: XD₂ = 65; XDT= 10; XT₂= 25; the accuracy of calculating the composition of the vapor phase is 10-10.Conclusions. The parameters of the binary energy interaction of the UNIQUAC model of hydrogen isotopic mixtures D2-T2, D2-DT, and DT-T2 are determined. The UNIQUAC model is adequate in relation to experimental data on the coefficient of separation. Due to systematic deviations in the theoretical Sherwood and ideal models, they are not suitable for further calculations of phase equilibrium of isotopic mixtures of hydrogen D2-T2, D2-DT, DT-T2, and D2-DT-T2.